PRIMA 2015: Principles and Practice of Multi-Agent Systems 18th International Conference, Bertinoro, Italy, October 26-30, 2015, Proceedings - Chen, Qingliang; Torroni, Paolo; Villata, Serena; Hsu, Jane; Omicini, Andrea (Lecture Notes in Artificial Intelligence, 2015)
This book constitutes the proceedings of the 18th International Conference on Principles and Practice of Multi-Agent Systems, PRIMA 2015, held in Bertinoro, Italy, in October 2015. The 29 full papers and 24 short papers presented in this volume were carefully reviewed and selected from 94 submissions. The conference brings together active researchers, developers and practitioners from both academia and industry to showcase, share and promote research in several domains, ranging from foundations of agent theory and engineering aspects of agent systems, to emerging interdisciplinary areas of agent-based research.